Population structure and emergence of resistance to new and repurposed drugs in XDR-TB: insights from a 10-year genomic study in the Western Cape, South Africa review - Ngom, Justice Tresor; Loubser, Johannes; Maasdorp, Elizna; Ghebrekristos, Yonas; Singh, Sarishna; Opperman, Christoffel J.; Klopper, Marisa; Warren, Robin Mark; Streicher, Elizabeth M. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundExtensively drug-resistant tuberculosis (XDR-TB) is a global health threat, being expensive and difficult to treat, with high mortality rates. The Western Cape Province (WCP), South Africa, has a particularly high burden of XDR-TB (>800 cases in the past ten years). Drug resistance genotypes and transmission present substantial regional variability. Thus, a better understanding of genetic diversity, clustering and the factors related to transmission can aid in prioritising resources to effectively target high-risk populations and regions that are disproportionately affected. We describe genetic diversity, drug resistance profiles and identify potential factors associated with the spread of XDR-TB strains collected in the WCP.MethodsWe included 729 XDR-TB samples (one per patient), identified through routine diagnosis spanning 2010 to 2019, from six healthcare districts (HCDs) in the WCP. Genomic DNA from cultured isolates was sequenced using the Illumina platform. Sequences were analysed for strain type, drug resistance mutations, and genomic clustering using the TBProfiler and MTBseq pipelines. We conducted logistic regression analysis to identify potential factors associated with genomic traits related to the spread of XDR-TB strains.ResultsOf the 729 XDR-TB strains, sublineage 2.2.2 (Atypical Beijing: n=378, 58.79%) strains were predominant, followed by Sublineage 2.2.1 (Typical Beijing: n=260, 40.43%). Atypical Beijing strains were more likely to cluster than Typical Beijing strains. Most of the clusters were small, with a few large and very large clusters, and the strains within very large clusters (primarily Atypical Beijing) were more likely to be found within Cape Town Metropole, Cape Winelands and Garden Route HCDs. Certain Atypical Beijing strains were found resistant to new and repurposed drugs recently introduced in the WHO treatment guidelines and clustered, indicating potential transmission.ConclusionsNear-untreatable Atypical Beijing strains are prevalent in the WCP. Hence, hotspot areas for clustering in Cape Town Metropole, Cape Winelands and Garden Route HCDs should be prioritised for targeted intervention to prevent ongoing XDR-TB transmission.